50 World-record writing prompts, Grades 3-6 - Martin, Justin McCory (New York : Scholastic Professional Books, 2001)
Super-motivating, reproducible prompts that use amazing world records as springboards to great writing.
Keywords: Elementary education -- Reading -- Juvenile literature